Hypocalcaemic cardiac failure. Issue 635 (September 1978) - Brenton, D. P.; Gonzales, J.; Pollard, A. B.
Abstract : A 35-year-old patient who presented with recurrent chest infection, pulmonary oedema and cardiac failure was found to be grossly hypocalcaemic owing to previously undiagnosed hypoparathyroidism. The cardiac failure was not easily relieved by digoxin and diuretics but it quickly responded when the plasma calcium was restored to normal with dihydrotachysterol. With dihydrotachysterol as sole treatment for more than 2.5 years he had normal exercise tolerance and no features of cardiac failure.